2011
DOI: 10.1186/1471-2458-11-768
|View full text |Cite
|
Sign up to set email alerts
|

Alimentary fluoride intake in preschool children

Abstract: BackgroundThe knowledge of background alimentary fluoride intake in preschool children is of utmost importance for introducing optimal and safe caries preventive measures for both individuals and communities. The aim of this study was to assess the daily fluoride intake analyzing duplicate samples of food and beverages. An attempt was made to calculate the daily intake of fluoride from food and swallowed toothpaste.MethodsDaily alimentary fluoride intake was measured in a group of 36 children with an average a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 24 publications
1
22
0
2
Order By: Relevance
“…When solid food and liquids are analyzed separately, less contribution from solids to the final fluoride intake average is observed [Oganessian et al, 2011], and that fact was confirmed in this study. The children's diet was composed mostly of crackers, bread, juice, milk, and water.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…When solid food and liquids are analyzed separately, less contribution from solids to the final fluoride intake average is observed [Oganessian et al, 2011], and that fact was confirmed in this study. The children's diet was composed mostly of crackers, bread, juice, milk, and water.…”
Section: Discussionsupporting
confidence: 73%
“…Studies of children in higher age groups in regions with temperate, subtropical, and tropical climates have observed a fluoride intake average below the results of this study [Rodrigues et al, 2009;Oganessian et al, 2011;Amaral et al, 2014]; in those case the cities had water with a fluoride concentration of 0.6-0.9 mg/l, being artificially or naturally fluoridated. With increasing age, the average fluoride intake tends to decrease due to the child's rising body weight and greater control over the expulsion of toothpaste remnants [Sohn et al, 2009].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In the past, this approach has been successfully used for the determination of fluoride ions in a number of foodstuffs (Kjellevold Malde et al, 2001;Oganessian et al, 2011;Ponikvar et al, 2007) since it provides some important advantages over other options, like the low cost of the apparatus, the simplicity of the analysis and its good sensitivity and Free fluoride determination in honey by ion-specific electrode potentiometry accuracy. One of the most significant steps involved in a reliable FISE method assessment is a proper choice of the TISAB solution, which should simultaneously fulfill different requirements, all aimed to maximize the amount of the free F À ion (i.e., the only form of fluorine that can be detected by FISE).…”
Section: Methods Assessmentmentioning
confidence: 99%
“…An attempt to reduce this limitation was made by collecting food samples on days that parents were at home, as was done in the study by Oganessian et al 31 Another advantage is diet stability, since on consecutive days the type of food eaten can be similar. An additional limitation is that the duplicate diet was collected by the caregiver.…”
Section: Discussionmentioning
confidence: 99%